TRAINING TECHNOLOGIES IN THE EDUCATION OF LYCEUM STUDENTS (ON THE EXAMPLE OF LYCEUMS OF SECURITY AND NATIONAL PATRIOTIC EDUCATION OF THE MINISTRY OF INTERNAL AFFAIRS OF UKRAINE) - Ievgen Bazhenkov; Halyna Kolomoiets; Natalia Divinska (Неперервна професійна освіта: теорія та практика)
The article highlights the specifics of the activities of security-oriented lyceums and national-patriotic education within the Ministry of Internal Affairs of Ukraine. It examines the potential for applying training methods and forms of work in the education of learners at security-oriented lyceums and national-patriotic education programs. It is established that in security-oriented lyceums, where future law enforcement officers and security service professionals are trained, training forms of work occupy a special place. These methods serve as a powerful tool for professional development and national-patriotic education, fostering the personal qualities essential for future service. An analysis of scientific sources has been conducted, enabling the definition of the concept of «training forms of work in the education of learners in security-oriented lyceums and national-patriotic education». The research outlines its goal and presents the experience of applying training methods and forms of work in the preparation of educators who teach learners in security-oriented lyceums and national-patriotic education programs. The study substantiates the effectiveness, highlights the advantages and disadvantages of using training in the educational process at these institutions. Recommendations are provided for pedagogical staff regarding the specific features of applying training forms and teaching methods in the educational process of security-oriented lyceums and in national-patriotic education.